ANALYZING OF SPATIAL STRUCTURE CHARACTERISTICS OF TROPICAL EVERGREEN FOREST STANDS UNDER ENVIRONMENTAL HETEROGENEITY - Hong Hai, Nguyen; Viet Duc, Vi (Journal of Forestry Science and Technology, 2020)
Structural complexity and local diversity of species-rich tropical forests can be characterized by their nearest neighbour characteristics. Aiming to describe spatial patterns, species mingling and dominance of species at fine spatial scales, we applied the quantitative analyses based on relationships of nearest neighboring trees. In two 1-ha plot of tropical evergreen forest stands in Babe National park, northern Vietnam, all tree individuals with diameter at breast height-DBH ≥ 2.5 cm were mapped and their characteristics (i.e., DBH and species) were recorded. The findings showed that: Most of studied species in the forests were highly mixed with other species, while conspecifics were regular to aggregated distribution but mainly focused at random pattern at small spatial scales. DBH dominance values ranged from low to high levels, except species including H. kurzii, S. wightianum and B. hsienmu completely dominated their neighbouring trees. We assumed the main ecological processes such as dispersal limitation and Neutral theory, regulating spatial structures of these forest stands. The spatial structural parameters offer direct and valuable information about spatial structure of forest stand as advantageous approaches. Those information can be used in thinning of sustainable forest management, modelling and restoration.